Medical and economic implications of strategies to prevent alloimmunization in sickle cell disease. Issue 9 (26th June 2017) - Gehrie, Eric A.; Ness, Paul M.; Bloch, Evan M.; Kacker, Seema; Tobian, Aaron A. R.
Abstract : BACKGROUND: The pathogenesis of alloimmunization is not well understood, and initiatives that aim to reduce the incidence of alloimmunization are generally expensive and either ineffective or unproven. In this review, we summarize the current medical literature regarding alloimmunization in the sickle cell disease (SCD) population, with a special focus on the financial implications of different approaches to prevent alloimmunization. STUDY DESIGN AND METHODS: A review of EMBASE and MEDLINE data from January 2006 through January 2016 was conducted to identify articles relating to complications of SCD. The search was specifically designed to capture articles that evaluated the costs of various strategies to prevent alloimmunization and its sequelae. RESULTS: Currently, there is no proven, inexpensive way to prevent alloimmunization among individuals with SCD. Serologic matching programs are not uniformly successful in preventing alloimmunization, particularly to Rh antigens, because of the high frequency of variant Rh alleles in the SCD population. A genotypic matching program could offer some cost savings compared to a serologic matching program, but the efficacy of gene matching for the prevention of alloimmunization is largely unproven, and large‐scale implementation could be expensive. CONCLUSIONS: Future reductions in the costs associated with genotype matching could make a large‐scale program economically feasible. Novel techniques to identify patients at highest risk for alloimmunization could improve the cost effectiveness of antigen matching programs. A clinical trial comparing the efficacy of serologic matching to genotype matching would be informative.